Nonlinear and time-dependent analysis of continuous unbonded prestressed concrete beams - Lou, Tiejiong (2013)
This paper describes a numerical model developed to predict the full-range nonlinear response, as well as time-dependent service-load behaviour, of continuous beams prestressed with internal unbonded tendons. Both geometric and material nonlinearities are considered. The strain increment in unbonded tendon, at any deformed state, is computed from the elongation of the entire tendon between end anchorages. The unbonded prestressing contributes to the concrete beam by equivalent loads, which would be updated continuously during the solution process. The analysis reproduces the experimental results of continuous beam specimens with favourable agreement. Some important aspects of behaviour of the continuous beams are examined.